(untitled) (Conferencea, 2024)
Today, 35-40 tons of small-fraction limestone waste is released as waste from the Kungirot soda enterprise located in the territory of Karakalpakstan of the Republic of Uzbekistan. This means that 12,775-14,600 tons of this type of waste are produced per year. Various physico-mechanical properties of concrete can be improved by adding these wastes to concretes as bulk aggregates in optimal compositions. In order to determine the reasons for the improvement of the physical and mechanical properties of the samples obtained on the basis of these wastes, the results of scanning electron microscope analyzes (SEM) were reported in the article.